Recomendaciones para el diagnóstico, manejo y prevención de la influenza en Chile: Período 2013 - Saldías P, Fernando (Revista Chilena de Enfermedades Respiratorias, 2013)
Influenza virus infection causes significant morbidity and mortality in Chile each year. The majority of persons infected with influenza virus exhibit self-limited, uncomplicated, acute febrile respiratory symptoms or are asymptomatic. However, severe disease and complications due to infection, including hospitalization and death, may occur in elderly and very young people, in those with underlying medical conditions (including pulmonary and cardiac disease, diabetes, and immunosuppression), in pregnant women and in previously healthy people. Early treatment with antiviral medications may reduce the severity and duration of symptoms, hospitalizations, and complications (otitis media, bronchitis, pneumonia), and may reduce the use of outpatient services and antibiotics, extent and quantity of viral shedding, and possibly mortality in certain populations. Vaccination is the best method for preventing influenza, but antivirals may also be used as primary or secondary means of preventing influenza transmission in certain settings. We review the main recommendations for the diagnosis, treatment and prevention of influenza in our country.